POTENTIAL ROLE PLAYED BY VISCOUS HEATING IN THERMAL-CHEMICAL CONVECTION IN THE OUTER CORE - Hansen U.; Yuen D.A. (My University, 1996)
There are increasing evidences to suggest that the composition of the outer-core is heterogeneous and consists of iron and other lighter elements. There is also some support of the likelihood for light elements to come out of the inner core. Such a release of potential energy can be converted into mechanical heat dissipated via the kinetic energy of the fluid motions in thermal-chemical convection. We have studied the possibilities of significant viscous heating from thermal-chemical convection in the outer core with a simple model. The results show that very high interior temperature can be produced by the efficient conversion of chemical potential energy to heat dissipated. The maximum temperature attained can exceed the temperature of the inner-outer core boundary for a chemical buoyancy ratio exceeding 5. This maximum temperature increases with the buoyancy ratio, which measures the relative strengths between chemical and thermal convective strengths. The amount of dissipative heat liberated from thermal-chemical convection may place constraints on the amount of heat produced by ohmic dissipation due to dynamo action in the outer core.